Interrogating Representation of Power Imbalance in Tim O’Brien’s The Things They Carried (Pursuits: A Journal of English Studies, 2025)
This paper explores the power imbalance between the American soldiers and Vietnamese soldiers as portrayed in Tim O’Brien’s The Things They Carried. The research aims to investigate about the unparalleled military powers of American and Vietnamese soldiers as depicted in the novel. Meanwhile its purpose is to explore the causes of military defeat on the part of the most powerful American soldiers. Despite military supremacy of the Americans, they are compelled to lose the lives of numerous soldiers in the combat because of the negligent and poor leadership. Cross’s recklessness leads the platoon to the defeat against the so-called powerless soldiers of Vietnam. The major finding is that technologies and resources cannot ensure the victory until and unless war strategies are functional and contextual as exemplified in the case of two imbalanced military powers: American soldiers and Vietnamese soldiers. Because of the effective strategies, Vietnamese soldiers do not lose much, while the supremacy as reflected in American arrogance is questioned because of terrible causalities. The research suggests that patriotism is acceptable but blind and hasty decisions lead people to massive defeats in life. The study has been based on interpretivism as a philosophical approach that inquires the meaning between the lines of the text.